Carbon footprint of laptops for export from China: empirical results and policy implications. (1st February 2016) - Liu, Jingru; Yang, Dong; Lu, Bin; Zhang, Jieqiong
Abstract: China's laptop exports account for more than 70% of global laptop shipments by volume. Laptop is a typical import-and-assembly processing trade product in the machinery and electrical equipment-manufacturing sector and comprises nearly 60% of China's total export value. The laptop sector is also carbon emissions intensive and contributes heavily to China's carbon emissions problem. To study the laptop sector's impact on carbon emissions, we first developed a carbon footprint map for the product across its supply chain, which allowed us to identify the emission contributions of each component and the production process as a whole. Then, using Simapro software and life cycle inventory data derived from the bottom-up life cycle-analysis method, we calculated the carbon footprint of laptop production. The results show that 33.3% of the carbon emissions from the production of export laptops originate from components produced abroad, while 66.7% is derived mainly from components produced domestically. Finally, we discuss the uncertainties in our approach and the trade policy implications of our research results. Highlights: Process-sum LCA provide a good framework for developing a detailed carbon process map of a product across the supply chain. Laptop is one of the most typical import-and-assembly processing trade product of China. 33.3% of the carbon emissions from export laptops originate mainly from components produced abroad, while 66.7% is mainly from components produced domestically.